Developing a visual model to represent the implementation of an ambitious mathematics program - Choppin, Jeffrey; Al, Saliha; Li, Junnan; Wilkes, Charles E.; Calleros, Ernesto Daniel (Frontiers in Education, 2025)
We describe the development of a visual model to represent the implementation of an ambitious mathematics program, which serves as an example of a complex educational reform. Visual models can be both conceptual and empirical, representing aspirational and theoretical perspectives while simultaneously incorporating empirical details specific to the context. Integrating conceptual and empirical aspects leads to tensions in managing the complexity of the model. Our process began with a simple model that guided our empirical work, which involved qualitative analysis. As we explored the systems and resources associated with the implementation of the ambitious mathematics program, the model took on more detail and complexity, both conceptually and empirically. In subsequent iterations of the model, we encountered tensions in balancing conceptual and empirical purposes, as well as challenges in displaying its emerging complexity.